1993
DOI: 10.1084/jem.177.5.1287
|View full text |Cite
|
Sign up to set email alerts
|

Malaria circumsporozoite protein binds to heparan sulfate proteoglycans associated with the surface membrane of hepatocytes.

Abstract: During feeding by infected mosquitoes, malaria sporozoites are injected into the host's bloodstream and enter hepatocytes within minutes. The remarkable target cell specificity of this parasite may be explained by the presence of receptors for the region II-plus of the circumsporozoite protein (CS) on the basolateral domain of the plasma membrane of hepatocytes. We have now identified these receptors as heparan sulfate proteoglycans (HSPG). The binding of CS to the receptors is abolished by heparitinase treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
234
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(239 citation statements)
references
References 50 publications
4
234
0
1
Order By: Relevance
“…Previous research found that some pathogens use a surface heparin-binding protein to bind the host cells (56)(57)(58)(59)(60)(61). However, no HBM was identified in SWP7 or SWP9.…”
Section: Discussionmentioning
confidence: 83%
“…Previous research found that some pathogens use a surface heparin-binding protein to bind the host cells (56)(57)(58)(59)(60)(61). However, no HBM was identified in SWP7 or SWP9.…”
Section: Discussionmentioning
confidence: 83%
“…Several lines of evidence suggest that this arrest is mediated by the interaction between the major surface protein of sporozoites, the circumsporozoite protein (CSP) and the highly sulfated HSPGs of hepatocytes [35][36][37][38][39]. Recombinant CSP binds specifically to hepatic HSPGs and in vivo, the physiologic ligands for hepatic HSPGs, namely lactoferrin and lipoprotein remnants, delay CSP clearance from the circulation and inhibit sporozoite infection of hepatocytes [40].…”
Section: To the Livermentioning
confidence: 99%
“…Lactoferrin (aa [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] CAVS QPETKCFQRNMRKI/R yoelii CS, apoE, and lactoferrin. Boldface italics indicate amino acid residues of CS protein required for binding to HSPGs (22).…”
Section: Rklrkrllrdaedlqkrla Vmentioning
confidence: 99%
“…Within minutes after intravenous injection into mice, CS accumulates in the space of Disse on the plasma membrane of hepatocyte microvilli (18). Heparinase treatment of liver sections that have been incubated with CS, and other in vitro experiments using hepatocytes and HepG2 cells as targets, demonstrate that CS binds to HSPGs (19,20). The proteoglycan-binding portion of CS (19,21) is region II-plus (22), a stretch of amino acids highly conserved in all species of malaria parasites (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation